Incidence and predictors of seizure-related injuries among epileptic patients undergoing follow-up treatment at public hospitals in Central Ethiopia - Selamawit Wondale Begizew; Bethelhem Birhanu Muluneh; Taye Mezgebu Ashine; Asnakech Zekiwos Heliso; Getachew Ossabo Babore; Elias Ezo Ereta; Sentayehu Admasu Saliya; Awoke Girma Hailu; Elias Nigusu Abdisa (Scientific Reports, 2025)
Abstract Seizure-related injuries represent a significant concern for both individuals with epilepsy and their caregivers. Compared to the general population, those diagnosed with epilepsy face a heightened risk of sustaining injuries. Despite this, there is a notable scarcity of data regarding seizure-related injuries among epileptic patients. This study aimed to evaluate the incidence of seizure-related injuries and identify their predictors among epileptic patients undergoing follow-up treatment at selected public hospitals in Central Ethiopia, in 2023. A prospective follow-up study was carried out in selected public hospitals in central Ethiopia. The study included epileptic patients aged ≥ 18 years who had not experienced any previous injury during follow-up treatment from January 1st, 2023, to December 31st, 2023. Data collection involved conducting interviews with participants using a structured questionnaire and reviewing patients’ charts. Univariate analysis, multivariate, and regression analysis were performed to identify potential associations between variables and seizure-related injuries. Variables were deemed significantly associated with seizure-related injuries if they attained a p value of 0.05 with a 95% confidence interval. Out of the 561 participants, 265 (47.2%) experienced seizure-related injuries (95% CI 43.12, 51.38). The incidence density rate of seizure-related injuries among epileptic patients was 11.97 per 100 person-months of observation (95% CI 10.61, 13.50). In multivariate analysis, epileptic patients who had generalized tonic–clonic seizures (adjusted hazard ratio 1.4, 95% CI 1.07–1.84), comorbidities (adjusted hazard ratio 1.3, 95% CI 1.11–1.71), were on polytherapy drug regimens (adjusted hazard ratio 1.80, 95% CI 0.30–2.49), and consumed alcoholic drinks (adjusted hazard ratio 1.5, 95% CI 1.21–1.89) were identified as independent predictors of seizure-related injuries. The incidence rate of seizure-related injuries among epileptic patients was found to be significant. Risk factors identified included experiencing generalized tonic–clonic seizures, having at least one additional health condition, being on multiple medications, and consuming alcohol. To improve survival from injuries, targeted precautions for generalized tonic–clonic seizures, strict adherence to prescribed medication regimens, and avoiding alcohol consumption are recommended.